1992
DOI: 10.1346/ccmn.1992.0400609
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cations on Imogolite and their Effect on Surface Charge Characteristics

Abstract: Abstract--Noncrystalline aluminosilicates termed allophane and imogolite are common constituents of spodosols, soils derived from volcanic ash, and many inceptisols. The surface charge characteristics of their synthetic analogues may be used to better understand their ion retention properties. In this study, we determined the point of zero salt effect (PZSE) by potentiometric titration of allophanes with A1/Si ratios of 1.12, 1.52, and 2.04 and of imogolite with an A1/Si ratio of 2.02. We also used microelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 23 publications
(26 reference statements)
3
43
0
1
Order By: Relevance
“…However, this is not the case. From electrolyte ion-adsorption data, the overall PZSE (point-of-zero salt effect) of imogolite has been estimated to be between pH 6-8 (Wada, 1989;Harsh et aL, 1992;Denaix et al, 1999). Imogolite may also sorb phosphate strongly (Theng et al, 1982;Clark and McBride, 1984).…”
Section: The Structure Of 1mogolitementioning
confidence: 99%
See 1 more Smart Citation
“…However, this is not the case. From electrolyte ion-adsorption data, the overall PZSE (point-of-zero salt effect) of imogolite has been estimated to be between pH 6-8 (Wada, 1989;Harsh et aL, 1992;Denaix et al, 1999). Imogolite may also sorb phosphate strongly (Theng et al, 1982;Clark and McBride, 1984).…”
Section: The Structure Of 1mogolitementioning
confidence: 99%
“…Harsh et al (1992) speculated that imogolite carried a weak structural positive charge. It is clear that such a structural charge cannot involve substitutions such as A1 for Si, because nuclear magnetic resonance (NMR) studies have shown imogolite to consist exclusively of hexavalent A1 and unpolymerized, tetravalent Si (Goodman et al, 1985;Ildefonse et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Imogolite is a unique clay mineral that disperses under acidic conditions and flocculates under alkaline conditions, where the net charge is considerably negative (Horikawa 1975;Harsh et al 1992;Karube 1998). Concerning the mechanism of this unique behavior, Horikawa (1975) discussed the idea that the effects of negative charge that arise at the inner surface of imogolite might be weakened at the outer surface because of the distance between the surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Karube et al (1992) reported that the mobility of imogolite toward the positive electrode was difficult to detect using a Briggs-cell due to the flocculation of the fibrous particles. Harsh et al (2002) and Tsuchida et al (2005) mentioned that cations may enter the tube and effectively neutralize the negative charge. Ma and Karube (2007) examined the effects of imogolite addition on the colloidal stability of montmorillonite and kaolinite, and confirmed that imogolite has no surface charge under alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Esses minerais metaestáveis são altamente reativos e pobremente cristalizados, sem um modelo ou estrutura definida. Tais fases amorfas afetam atributos físicos, químicos e biológicos dos solos (SU et al, 1992;KARUBE et al, 1992;HARSH et al, 1992). um metal e um ânion por óxidos, hidróxidos e óxi-hidróxidos de alumínio desempenham um papel importante no controle da mobilidade desses ânions no solo (HUANG et al, 2002;PARFITT, 1978).…”
Section: Mineralogia Do Solounclassified